Evaluation of Resident Physicians' Knowledge of and Attitudes Towards Prescribing Buprenorphine for Patients With Opioid Use Disorder. Issue 3 (May 2021) - Shuey, Bryant; Lee, Dasom; Ugalde, Israel; Borgan, Saif; Bresnan, Caroline; Qureshi, Marvi; Mhaskar, Rahul; Oxner, Asa
Abstract : Objective: To determine internal medicine (IM) residents' knowledge of, attitudes towards, and barriers to prescribing buprenorphine for opioid use disorder (OUD). Methods: We conducted a cross-sectional study of IM residents across all 35 Accreditation Council for Graduate Medical Education (ACGME) accredited Florida IM residency programs. We used an online survey to collect information about resident demographics, substance use curriculums, career interests, content knowledge about diagnosing and managing OUD, and attitudes about and barriers to prescribing buprenorphine for OUD. We used Chi-square test to explore differences in interest in prescribing buprenorphine. We created a composite knowledge score and investigated distribution of knowledge among characteristics via Mann-Whitney U test. Results: There were 161 participants (response rate 16.0%, n = 1008) across 35 programs Seventy-seven percent of residents provided care for patients with OUD more than once per month. Seventy-four percent report no buprenorphine prescribing training. Higher knowledge scores, interest in primary care, being an intern, and caring for patients with OUD more than monthly were associated with interest in obtaining a buprenorphine waiver ( P  < 0.05). Limited knowledge about OUD was the most important barrier to prescribing buprenorphine. Eighty-nine percent support legislation to deregulate buprenorphine. Conclusions: Knowledge about managing OUD was poor and represented the most commonly cited barrier to prescribing buprenorphine. Residents want to expand their role in treating OUD. Our findings warrant incorporating addiction medicine into residency curriculum standards. Legislation removing the buprenorphine waiver requirement may increase the number of resident buprenorphine prescribers and improve treatment options for patients with opioid addiction. Abstract : Supplemental Digital Content is available in the text